Kyra gen. nov. (Cicadellidae,Deltocephalinae) e descrições de duas novas espécies - Zanol, Keti M. Rocha (Acta Biológica Paranaense, 2011)
<htm>Kyra gen. nov. (Cicadellidae,Deltocephalinae) e descrições de duas novas espécies </htm>